Comprehensive Genome-Wide Analysis of Thaumatin-Like Gene Family in Four Cotton Species and Functional Identification of GhTLP19 Involved in Regulating Tolerance to Verticillium dahlia and Drought - Li, Zhanshuai; Wang, Xiaoyan; Cui, Yupeng; Qiao, Kaikai; Zhu, Longfu; Fan, Shuli; Ma, Qifeng (Frontiers in Plant Science, 2020)
Thaumatin-like proteins (TLPs) present in the form of large multigene families play important roles in biotic stress and abiotic stress. However, there has been no systematic analysis of the TLPs in cotton. In this study, comprehensive identification and evolutionary analysis of TLPs in four species of cotton were conducted. In total, 50, 48, 91, and 90 homologous sequences were identified in Gossypium raimondii, G. arboreum, G. barbadense, and G. hirsutum, respectively. Gene structure, protein motifs, and gene expression were further investigated. Transcriptome and quantitative real-time PCR analysis indicated that GhTLPs participate in abiotic, biotic stress and cotton fiber development. GhTLP19 on chromosome At05 was selected as a candidate gene for further study. When GhTLP19 was silenced by virus-induced gene silencing (VIGS) in cotton, with the increase of malondialdehyde (MDA) content and the decrease of catalase (CAT) content, and as the increase of disease index (DI) and hyphae accumulation, the plants were more sensitive to drought and Verticillium dahliae. Furthermore, the GhTLP19 overexpressing Arabidopsis transgenic lines exhibited higher proline content, thicker and longer trichomes and more tolerance to drought when compared to wild type. This study will provide a basis and reference for future research on their roles in stress tolerance and fiber development.